The Paradigm of Religious Moderation: Interpreting the Concept and Characteristics - Muhammad Royyan (Jurnal Indonesia Studi Moderasi Beragama, 2024)
Religious moderation must be understood contextually not textually, meaning that moderation in religion in Indonesia is not a moderate Indonesia, but an understanding of religion must be moderate. The purpose of this research is to find out the basic concepts of religious moderation and the characteristics contained in it. This type of research uses a descriptive qualitative, research method uses a literature review. The data collection method uses documentation. Researchers use content analysis techniques. The results concluded that religious moderation provides an understanding that as a Muslim tolerating fellow religious people, and not discriminating between races, ethnicities, and religions, also teaches how we think dynamically and innovatively. This moderation concept will bring Indonesia in a better direction, so that there is no discrimination in diversity and creates a sense of security and comfort. This research contributes as enrichment material and knowledge information for readers and academics related to the urgency of the concept (paradigm) of religious moderation and its implications in everyday life.